PENYULUHAN KESEHATAN TENTANG GIZI SEIMBANG DALAM RANGKA MENGATASI STUNTING DI TPQ TAHFIDZ NURUSSALAM - Nurul Aryastuti; Yolandha Adinda Pratiwi; Sri Wulandari; Farra Hayka Salsabilla; Renna Oktavia Rudi (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Balanced nutrition is a daily food composition containing nutrients in the type and amount according to the body's needs, taking into account the principles of food diversity, physical activity, clean living behavior, and monitoring body weight regularly in order to pay attention to normal weight to prevent nutritional problems. The purpose of this counseling activity is so that respondents can know, understand about balanced nutrition and stunting. The method used in health education about balanced nutrition in order to overcome stunting at Tahfidz Nurussalam TPQ was carried out in 3 stages, firstly, the students of the Public Health Study Program distributed posters about balanced nutrition, the two presenters explained about balanced nutrition using poster media and also presentations in the form of video, and the three students of the Public Health Study Program asked and answered questions about the material that had been delivered. After the counseling was carried out, the children of TPQ Tahfidz Nurussalam could understand about balanced nutrition and stunting. From these activities, it was concluded that it was important to provide nutrition/nutrition to children in accordance with the nutritional adequacy rate for children whose purpose was to process children's growth and development.